An investigation into stylistic devices in “oxford thƣơng yêu” by duong thuy and their english translational equivalents by elbert bloom - Lê,Thị Mỹ Hạnh. (2016)
This thesis focused on identifying and analyzing stylistic devices commonly used in “Oxford thƣơng yêu” by Duong Thuy and their English translational equivalents in „„Beloved Oxford" by Elbert Bloom to discover their similarities and differences of using stylistic devices in the two versions. The data of the study were collected from “Oxford thƣơng yêu" by Duong Thuy and “Beloved Oxford" by Elbert Bloom. All datas were described and contrastively analyzed in stylistic aspects with qualitative and quantitative approaches to yield more precise points on stylistic devices used in literary language. On the basis of the contrastive analysis, we realized that stylistic devices have a strong effect on the two works and the differences of using them make the meaning change in some cases. This thesis focused on analyzing some stylistic devices commonly used in the two works “Oxford thƣơng yêu” by Duong Thuy and “Beloved Oxford" by Elbert Bloom namely Onomatopoeia, Simile, and Repetition to compare the loss and gain of meaning in the process of stylistic devices translation. With the findings in the two works, some suggestions have been partly proposed to contribute to better teaching, learning English as a foreign language, specifically the awareness of learners in using stylistic devices for interpreting and writing literary works. For teaching, teachers can encourage students to apply as many stylistic devices are possible to beautify their writing. Students should know how to choose and use them properly in each speech act. Moreover, they will know how the writers use stylistic devices to understand deeply the meaningful message which the author wants to convey in literary works.